P11.53.B Efficacy and tolerability of regorafenib in pretreated patients with progressive CNS grade 3 or 4 gliomas. (5th September 2022) - Werner, J; Wolf, L; Tscherpel, C; Bauer, E K; Wollring, M; Ceccon, G; Deckert, M; Brunn, A; Pappesch, R; Goldbrunner, R; Fink, G R; Galldiks, N
Abstract: Background: The phase 2 REGOMA trial suggested an encouraging overall survival benefit in glioblastoma patients at first relapse treated with the multikinase inhibitor regorafenib. Here, we evaluated the efficacy and side effects of regorafenib in a real-life setting. Material and Methods: From 2018-2021, 30 patients with progressive WHO CNS grade 3 or 4 gliomas treated with regorafenib (160 mg/d; first 3 weeks of each 4-week cycle) with individual dose adjustment depending on toxicity were retrospectively identified. Side effects were evaluated according to the Common Terminology Criteria for Adverse Events (version 5.0). MRI was obtained at baseline and after every second cycle. Tumor progression was assessed according to RANO criteria. After regorafenib initiation, the median progression-free survival (PFS) and overall survival (OS) were calculated. Results: The median number of treatment lines before regorafenib was 2 (range, 1-4). The majority of patients (73%) had two or more pretreatment lines. At first relapse, 27% of patients received regorafenib. A total of 94 regorafenib cycles were administered (median number of cycles, 2; range, 1-9 cycles). Grade 3 and 4 side effects were observed in 47% and 7% of patients, respectively, and were not significantly increased in patients with two or more pretreatments (P>0.05). The most frequent grade 3 or 4 side effects were laboratory abnormalities (62%). PFS was 2.6 months (range, 0.8-8.2 months), and the OS was 6.2 months (range, 0.9-24 months). Conclusion: In patients with progressive WHO grade 3 or 4 gliomas, predominantly with two pretreatment lines or more, regorafenib seems to be effective despite considerable grade 3 or 4 side effects.